2007
DOI: 10.1007/s10533-007-9130-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in nutrient concentrations of the Changjiang River and principal tributaries

Abstract: We present long-term nutrient data on the Changjiang River (Yangtze River) at six hydrological stations and eight principal tributaries during the period . Three patterns of temporal changes were observed in nitrateðNO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 35 publications
7
51
0
3
Order By: Relevance
“…These facts indicate mineral fertilizers, which are increasingly used in farming as KNO 3 salt, as the origin of the high NO 3 − and K + loads. This is in agreement with the assessments of Yan et al (2003) and Duan et al (2007). The river is supplied by groundwater during low-flow period in the middle and lower basin, where nitrate levels are higher than in the upper basin.…”
Section: Nutrients: N and Psupporting
confidence: 92%
See 3 more Smart Citations
“…These facts indicate mineral fertilizers, which are increasingly used in farming as KNO 3 salt, as the origin of the high NO 3 − and K + loads. This is in agreement with the assessments of Yan et al (2003) and Duan et al (2007). The river is supplied by groundwater during low-flow period in the middle and lower basin, where nitrate levels are higher than in the upper basin.…”
Section: Nutrients: N and Psupporting
confidence: 92%
“…Duan et al (2007) Today, we observed DIP concentrations on a much lower and constant concentration of 6-8 µgP/L compared to 10-25 µgP/L reported by Zhang et al (1999) a decade ago. However, contrary to the prior observations, NO 3 − concentrations steadily increased downstream of the TGD (Fig.…”
Section: Nutrients: N and Pmentioning
confidence: 53%
See 2 more Smart Citations
“…It is reported that the levels of nitrate throughout the Yangtze River system remained fairly constant before 1970s (Duan et al 2007). Recent results, however, showed that at the mouth of the Yangtze River the nitrate concentration has increased about three-fold in 40 years, from 1.3 mg l -1 in the 1960s to 3.7 mg l -1 in the 1980s and to 5.0 mg l -1 in 1990-2004.…”
Section: Nutrient Enrichment In China's Surface Watersmentioning
confidence: 99%